Performance of Concrete Incorporating of Clam Shell as Partially Replacement of Ordinary Portland Cement (OPC) - Kassim, Umar; Poh Ong, Bee (Journal of Advanced Research in Applied Mechanics, 2020)
In Malaysia, the uses of concrete will be demand higher in future due to growing of construction industry. Ordinary Portland cement (OPC) known as dominant precursor in manufacturing of concrete, every tons of OPC produce will released similar amount of carbon dioxide (CO2) in activities of quarrying limestone and calcination. Clam shells known as fishery industry waste that have high potential as partial cement replacement in concrete due to its similar chemical composition with limestone which is used in manufacturing of Portland cement. Clam shells were prepared by cleaning, crushing, grinding and calcination. This study investigate the performance of concrete using clamshells as partial replacement of OPC. The properties of clam shell concrete such as density, water absorption, compressive strength and splitting tensile strength has been studies. These properties were compare with Ordinary Portland cement (OPC) concrete. Based on mixes using clamshells ash with proportion of 4%, 6%, and 8% by weight of cement, the optimum compressive strength was achieved for the mix that replaced cement by 6%. The clamshells concrete has higher compressive strength and density compare to OPC in 28th days. For splitting tensile strength on 28th days specimens SC 6% has highest splitting tensile strength compare to specimens SC 4% and SC 8% but splitting tensile strength for OPC concrete (5.1MPa) is higher than specimens concrete SC 6% (4.4MPa). Future studies for this research are first studies into the analysis between degrees of calcination should be made to quantify the value and assesse durability testing of seashell concrete other than water absorption test.